ANALYSIS OF ROUTING PROTOCOLS IN FLYING WIRELESS NETWORKS - Natarajan, Krishnaraj (IRO Journal on Sustainable Wireless Systems, 2019)
The wireless network that are formed on the fly, without relying on the previous infrastructure, including the autonomous devices that lie nearby are called the flying wireless networks. Despite of the networks, self-configuring and selfhealing nature, it incurs many challenges due to its mobile nature, limited battery span and the lack of the centralized control, so these wireless network requires a perfect routing protocol addressing the challenges and improving the performance of the network, so the paper presents the survey on the various routing protocols that enhances the performance of the flying wireless network. The survey is further continued with the analysis of the routing protocols to evince the capability of the same on the grounds of network life time, energy consumption and the quality of service.